Unexpected Formation of Bis(hydrazinecarboximidamide) via Ultrasound Promoted Rearrangement of Epoxy Ketone - Brasil, Silvania Rizzi; Capiotto, Adriana do Carmo; Flores, Alex Fabiani Claro; Back, Davi Fernando; Faoro, Eliandro; Pizzuti, Lucas (Orbital: The Electronic Journal of Chemistry, 2017)
An efficient synthesis of aromatic pyrazoles via cyclocondensation of epoxy chalcones with hydrazine is reported. When aminoguanidine hydrochloride is the dinucleophilic specie the reaction leads to a mixture of amidino pyrazole and a minor amount (15%) of an interesting co-product identified as 2,2'-(1,3-diphenylpropane-1,2-diylidene)bis(hydrazinecarboximidamide) dihydrochloride by X-ray diffraction and NMR. A plausible mechanism for the co-product formation via rearrangement of the epoxy chalcone into 1,2-diketone followed by the condensation with aminoguanidine reaction is proposed.DOI: http://dx.doi.org/10.17807/orbital.v9i3.972